Human-Animal Interactions at Zoological Institutions - Marion, Christopher (My University, 2011)
Objective – To determine the preventive practices concerning zoonotic disease transmission between humans and animals in interactive exhibits at Association of Zoos & Aquariums (AZA) accredited institutions. Data were also analyzed to determine if annual budget was associated with particular preventive measures among the institutions. Design – Cross-sectional questionnaire. Participants –AZA accredited zoos and aquariums from across the United States and Canada. Procedures – A questionnaire, approved by the AZA’s Animal Health Committee, was distributed electronically to 166 institutions from the 2008 AZA list of accredited institutions. Responses were collected, tallied according to grouping by annual budget, and analyzed using Chi-square analysis to determine independence. Results – Forty-four of 166 (26.5%) of questionnaires were returned with data. The data indicated that all but one of 40 (97.5%) institutions with petting zoos provided hand sanitation, either via running water and soap or sanitizing gel at the exhibit exit. However, only half (17 of 34) of walk-through aviaries had some form of hand sanitation available at the exhibit exit. Only 17 of 40 (42.5%) petting zoos and 5 of 34 (14.7%) walk-through aviary exhibits had signs posted warning of the zoonotic dangers. Minor bite wounds associated with an aviary exhibit were reported from one institution, which was the only associated illness with either the petting zoo or walk-through aviary exhibits in this questionnaire. There were no statistical relationships between budget category and reported preventive measures. Conclusions – Respondents had many practices already in place to minimize the risk of disease transmission to visitors. Institutions should evaluate their current preventive measures with regards to this questionnaire and make modifications as necessary. One area many institutions should add to their current practices is disinfecting interactive exhibit barriers that the public can contact, to remove potential zoonotic organisms. This questionnaire found 4 institutions were not vaccinating mammals in interactive exhibits for rabies. The subsequent risk posed to visitors is one easily avoided. Twenty-three institutions with petting zoos did not have signs warning of the zoonotic dangers, and risky practices (eg, leaving animals on exhibit with loose stool) were reported by 8 petting zoo institutions. Some form of hand sanitation, preferably soap and sinks with running water, and signs educating visitors of the zoonotic potential were missing at many walk-through aviaries in this questionnaire, despite the fact that all 34 institutions with aviaries reported visitors may contact feces in the exhibit. No relationships between budget category and reported preventive measures were found, indicating that none of these measures were cost prohibitive to institutions with these types of exhibits.
Keywords: Zoonosis; Public Health; Petting zoo; Aviary; Human-animal interaction; Public Health (0573)